Model Pencatatan Keuangan pada Pelaku Usaha Mikro Kecil dan Menengah dengan Pencatatan Akuntansi - Deskys, Tri Rasid (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Accounting is the activity or process of recording, identifying, clarifying, managing, and presenting data related to a transaction. Accounting is also used as a basis for making appropriate decisions related to the financial condition of the company by using information about the company's value and information about profit / profit. Recordings have become one of the main activities in accounting. Once a transaction is identified, the company will record the transaction in the form of a financial report before communicating the outcome of the record to the parties who need the information report, both internal and external parties of the company. The purpose of the writing of this scientific paper is to obtain results of the importance of transaction documents in the process of accounting recording that will be included in the GF-Accounting program. The suggestion that would be given from this research so that the company can carry out the documentation of every daily transaction and directly record it into the GF-Accounting program so that there is no accumulation at the time of financial reporting.